Color Image Landscape Photo Hand-Painted Effect Evaluation with PFA Algorithm. (10th December 2021) - Liu, Shizhang
Abstract : With the continuous development of society and economy, diversified presentation and publicity of landscape are becoming more and more popular among the public, such as using color pictures to display multimedia publicity videos or APP, WeChat public accounts, and other new media. There are various ways of expression. Against the limitations of color image landscape, this article introduced the PFA algorithm, during the experiment of hand-painted landscape pictures, the effect of color hand-painted images is evaluated by using the coordination degree of natural target detection scene, and the corresponding image evaluation index values are obtained for effective analysis, and the prediction model is established. The simulation results show that the PFA algorithm is effective and can support the evaluation of the hand-painted effect of color landscape photos.